Hang 'em high law and disorder in western films and literature - Herzberg, Bob, 1956- (McFarland & Co., Inc., Publishers, 2013)
"This book discusses the many Western films as well as the novels they are based on, that illustrate distortions of the law in the Old West and the many ways, most of them marked by vengeance, in which its characters pursued justice"--